Immobilization and Stabilization of Beta-Xylosidases from Penicillium janczewskii - Terrasan, César Rafael Fanchini [UNESP]; Romero-Fernández, Maria; Orrego, Alejandro H.; Oliveira, Sandro Martins; Pessela, Benevides Costa; Carmona, Eleonora Cano [UNESP]; Guisan, José Manuel (Springer Nature, 2017)
β-Xylosidases are critical for complete degradation of xylan, the second main constituent of plant cell walls. A minor β-xylosidase (BXYL II) from Penicillium janczewskii was purified by ammonium sulfate precipitation (30% saturation) followed by DEAE-Sephadex chromatography in pH 6.5 and elution with KCl. The enzyme presented molecular weight (MW) of 301 kDa estimated by size exclusion chromatography. Optimal activity was observed in pH 3.0 and 70–75 °C, with higher stability in pH 3.0–4.5 and half-lives of 11, 5, and 2 min at 65, 70, and 75 °C, respectively. Inhibition was moderate with Pb+2 and citrate and total with Cu+2, Hg+2, and Co+2. Partially purified BXYL II and BXYL I (the main β-xylosidase from this fungus) were individually immobilized and stabilized in glyoxyl agarose gels. At 65 °C, immobilized BXYL I and BXYL II presented half-lives of 4.9 and 23.1 h, respectively, therefore being 12.3-fold and 33-fold more stable than their unipuntual CNBr derivatives (reference mimicking soluble enzyme behaviors). During long-term incubation in pH 5.0 at 50 °C, BXYL I and BXYL II glyoxyl derivatives preserved 85 and 35% activity after 25 and 7 days, respectively. Immobilized BXYL I retained 70% activity after 10 reuse cycles of p-nitrophenyl-β-D-xylopyranoside hydrolysis.
Keywords: Enzyme characterization; Enzyme immobilization; Enzyme purification; Enzyme stabilization; Penicillium janczewskii; β-Xylosidases